Evaluation of the effects of thyroid functions on frailty in geriatric patients using the Edmonton, SOF and FRAIL Scales - Galip Can Uyar; Mustafa Kemal Kılıç (BMC Geriatrics)
Abstract Background and rationale Thyroid dysfunction in older adults often mimics the signs of aging, impacting metabolism and overall physiological balance. While age-related chronic conditions have been extensively studied, the relationship between thyroid function and frailty remains underexplored. Objective This study aimed to evaluate the effects of thyroid dysfunction on frailty among individuals aged 65 years and older. Thyroid-stimulating hormone (TSH), free triiodothyronine (fT3), free thyroxine (fT4), and thyroid peroxidase antibody (anti-TPO) levels were analyzed. The study further examined the correlation between thyroid dysfunction, chronic diseases, sociodemographic factors, and optimal TSH levels in relation to frailty, using the Study of Osteoporotic Fractures (SOF), Edmonton Frail Scale (EFS), and FRAIL scales. Methods This cross-sectional study included 220 older adults with either treated or untreated thyroid dysfunction. Comprehensive geriatric assessments were conducted, including detailed medical histories, sociodemographic data collection, and thyroid function tests. Frailty was assessed using the SOF, EFS, and FRAIL scales. Multivariate logistic regression analyses were performed to identify significant associations between thyroid parameters and frailty. Results The median age of participants was 73 years, and 68.2% (n = 150) were women. Frailty prevalence was significantly higher in individuals with abnormal TSH levels (outside the 0.5–6 mIU/L range). Lower fT3 levels and the fT3/fT4 ratio were significantly associated with frailty, particularly as assessed by the SOF and EFS scales. In contrast, the FRAIL scale revealed a significant association between increased frailty and lower fT3 levels only. Subgroup analysis indicated that in individuals aged ≥ 80 years, a lower fT3/fT4 ratio was consistently associated with frailty across all frailty scales, whereas in those aged < 80 years, lower TSH levels showed a strong association with frailty as assessed by the FRAIL scale. These findings underscore age-specific variations in the relationship between thyroid function and frailty. Conclusion This study highlights the significant impact of thyroid dysfunction on frailty in older adults. Lower fT3 levels and the fT3/fT4 ratio emerged as key indicators of increased frailty, particularly on the SOF and EFS scales. Subgroup analysis further emphasized the importance of age-specific assessments, with a lower fT3/fT4 ratio being a critical indicator of frailty in individuals aged ≥ 80 years, while lower TSH levels were significant in those aged < 80 years. Abnormal TSH levels were strongly associated with frailty on the SOF scale, suggesting the need to consider thyroid dysfunction as a modifiable risk factor. Additionally, factors such as age, sex, education, thyroid medication use, and comorbidities influenced frailty status. Incorporating thyroid function tests into frailty assessments could enhance early identification and targeted interventions for at-risk older adults, particularly when age-specific thresholds are applied.